Water Resource Management through the Lens of Planetary Health Approach (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Despite recent progress in developing new strategies, practices and technologies for water resource management, their dissemination and implementation have been limited. The nexus approach encompasses these interdependencies, and to promote this idea, different global frameworks are there to address global health in a holistic and comprehensive ways, such one earth, one health, eco-health, planetary health, etc. Planetary health is the most recent one advocated by the scientific communities as well as policy makers, however, very little has been done to present empirical scientific evidence from the ground. Considering the above-mentioned information gap, this special issue aimed to capture the persistently changing dimensions and new paradigms of water security, providing a holistic view including a wide range of sustainable solutions to address water security at different landscapes.